Expression and characterization of phytoglobin genes from sugar beet (Beta vulgaris L.) in tobacco (Nicotiana benthamiana) - Ögell Benediktsson, Axel Carl-Vilhelm (SLU/Dept. of Plant Breeding (from 130101), 2016)
Phytoglobin is a plant globin protein similar to hemoglobin, which is found in all vertebrates. Phytoglobin is categorized depending on its origin and characteristics into 6 different classes: phytoglobin class 0, phytoglobin class 1, phytoglobin class 2, symbiotic phytoglobin, legphytoglobin and phytoglobin class 3. A recent study has identified two class 1 phytoglobin genes, BvHb1.1 and BvHb1.2, in Beta vulgaris that has not been functionally characterized so far. In the current study, the synthesized genes BvHb1.1 (BvPb1.1) and BvHb1.2 (BvPb1.2) were cloned into a tobacco mosaic virus based viral vector. The resulted plasmids were sequence-confirmed and transferred into Agrobacterium tumefaciens strain GV3101. The transformed A. tumefaciens was agrosprayed into Nicotiana benthamiana leaves along with a vector (pJL3:p19) containing the tomato bushy stunt virus (TBSV) gene-silencing suppressor (P19). Transiently expressed heterologous proteins in N. benthamiana were confirmed by SDS-PAGE and spectrophotometry. The spectrophotometric analysis showed that heterologously produced phytoglobins were functional as both proteins exhibited oxygen (O2) and carbon monoxide (CO) binding properties. This suggests that the transient expression using viral vector in N. benthamiana has great potential to be used for the production of plant proteins at industrial scale.